2014 International Conference on Unmanned Aircraft Systems (ICUAS) 2014
DOI: 10.1109/icuas.2014.6842314
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicle security using Recursive parameter estimation

Abstract: The proliferation of Unmanned Aerial Vehicles (UAVs) raises a host of new security concerns. Our research resulted in a prototype UAV monitoring system, which captures flight data and performs real-time estimation/tracking of airframe and controller parameters utilizing the Recursive Least Squares Method. Subjected to statistical validation and trend analysis, parameter estimates are instrumental for the detection of some classes of cyber attacks and incipient hardware failures that can invariably jeopardize m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…We observed that the focus of the investigated literature is mainly on Industry 4.0, even if in this field highly varying scenarios are considered. For example, some articles discuss petrochemical plant management [246], while others focus on drones [177], [192], [199], and so on. Each of these scenarios has its own threat model and will thus also differ in terms of security requirements from the others, to a certain degree.…”
Section: Iiot Security Requirements (Rq1)mentioning
confidence: 99%
“…We observed that the focus of the investigated literature is mainly on Industry 4.0, even if in this field highly varying scenarios are considered. For example, some articles discuss petrochemical plant management [246], while others focus on drones [177], [192], [199], and so on. Each of these scenarios has its own threat model and will thus also differ in terms of security requirements from the others, to a certain degree.…”
Section: Iiot Security Requirements (Rq1)mentioning
confidence: 99%
“…The paper authored by Zachary Birnbaum et al describes a solution for security in UAVs based on Recursive Parameter Estimation [13]. The authors start by identifying several UAV threats, like malicious hardware, hardware failures, attacks both against the communications channel and the flight control computer and attacks against the ground control station.…”
Section: A Study Of the State Of The Artmentioning
confidence: 99%
“…[15], [41], [42], [43], [44] Command Injection Request execution of existing command with malicious intent, typically to affect actuation [30], [15], [31], [32] Impersonation (or masquerade or spoofing) attack An adversary assumes successfully the identity of one of the legitimate nodes in the vehicular network [41], [45], [44], [46], [36], [47], [48], [49] Packet Duplication Transmit unnecessary network messages to exhaust bandwidth or trigger unnecessary processing [24], [23], [25] Selective Forwarding Retransmit data selectively in a vehicular network [24], [23], [25] GPS Jamming Jam legitimate GPS signals; possibly followed by GPS spoofing [28] GPS Spoofing Transmit false GPS signals to disrupt or hijack navigation of a GPSdependent vehicle, such as a UAV [28] Fuzzing (Fuzz testing) Send random messages to the in-vehicle network to trigger critical instructions in a brute force manner) [21] False Data Injection Transmit false data to trigger malicious events or affect situational/environmental awareness [28] False Information Dissemination Transmit false data, e.g. a reputation score, to affect a collaborative process in a network [28], [50] Location Spoofing Share false location coordinates within a vehicular network [39] Malware Infect vehicle with malicious software/firmware by compromising supply chain or hijacking an update [30], [51], [52], [19], [53] Resource exhaustion attack Exhaust a vehicle's battery/fuel, network, processing or other resource by repeating requests, infecting with malware, etc.…”
Section: Attackmentioning
confidence: 99%
“…Maliciously craft input data to sensors specifically aiming to affect its machine learning policies [56] Hardware Tampering Tamper with hardware or gain physical access to modify/damage components or infect with malware [51] Hardware Failure Physical damage or natural degradation of a vehicle's components [51] Fraudulent ADS-B Messages Transmit false ADS-B messages to affect aircraft safety [57], [58] AIS spoofing Transmit false AIS signals to impede vessel tracking [59], [60], [61] Isolation attack Isolate a node from a network by dropping all messages going to or coming from it…”
Section: Attackmentioning
confidence: 99%